Facilitation of 9, 10-phenanthrenequinone-elicited neuroblastoma cell apoptosis by NAD(P)H:quinone oxidoreductase 1. (5th January 2018) - Matsunaga, Toshiyuki; Kamase, Kyoko; Takasawa, Hiroaki; Yamaji, Yukiko; Endo, Satoshi; El-Kabbani, Ossama; Ikari, Akira
Abstract: 9, 10-Phenanthrenequinone (PQ), a major quinone component in diesel exhaust particles, is considered to provoke damage of respiratory and vascular cells through highly producing reactive oxygen species (ROS), but little is known about its pathophysiological role in neuronal cell damage. In this study, we found that incubation with 1, 2-naphthoquinone, 1, 4-naphthoquinone and PQ, major quinone components in diesel exhausts, provokes apoptosis of human neuroblastoma cell lines. SK-N-SH cell treatment with a lethal concentration of PQ facilitated ROS production within 6 h. The treatment also promoted formation of 8-hydroxy-deoxyguanosine, p53 activation, elevation of Bax/Bcl-2 ratio, lowering of mitochondrial membrane potential, and resultant activation of caspase-9 and caspase-3, inferring that ROS production, DNA damage and mitochondrial dysfunction are crucial processes of the PQ-triggered SK-N-SH cell apoptosis. The PQ treatment of SK-N-SH cells elevated the level of 4-hydroxynonenal (HNE), a cytotoxic reactive aldehyde generated from lipid peroxidation. The treatment with PQ and HNE also decreased cellular levels of total and reduced glutathiones, and the damage elicited by HNE was ameliorated and deteriorated by pretreating with cell-permeable glutathione analog and the depletor, respectively. Moreover, the treatment with PQ and HNE decreased the proteasomal proteolytic activities, suggesting a contribution of decrease in the antioxidant abilities to the ROS-mediated neuroblastoma cell apoptosis. Our comparative analyses of 17 cells showed a positive correlation between the PQ reductase and NAD(P)H:quinone oxidoreductase 1 (NQO1) activities. In addition, overexpression and knockdown of NQO1 augmented and lowered, respectively, the ROS production through PQ redox-cycling and the quinone toxicity. Furthermore, the treatment with PQ and HNE up-regulated the NQO1 expression. Taken together, PQ exposure produces large amounts of ROS in neuroblastoma cells via NQO1 up-regulation and resultant acceleration of its redox-cycling, followed by activation of the ROS-dependent apoptotic mechanism. Graphical abstract: Highlights: Treatment with 9, 10-phenanthrenequinone (PQ) induces neuroblastoma cell apoptosis. The apoptotic mechanism by PQ includes ROS formation and mitochondria dysfunction. PQ treatment promotes 4-hydroxynonenal formation and decreased glutathione level. NQO1 accelerates redox-cycling of PQ and augments cytotoxicity of the quinone. Expression of NQO1 is up-regulated by treatments with PQ and 4-hydroxynonenal.